A Study of Wuthering Heights from the Perspective of Eco-Criticism - Fatemeh Sadat Basirizadeh; Mahnaz Soqandi; Narges Raoufzadeh; Narges Zarei; Abdurahman Adisaputera (BIRCU, 2020)
This research paper attempts to explore the novel, Wuthering Heights, through the lens of Eco criticism and it explores the relationship between human and nature in the novel. Literature can be perceived as an aesthetically and culturally constructed part of the environment, since it directly addresses the questions of human constructions, such as meaning, value, language, and imagination, which can, then, be linked to the problem of ecological consciousness that humans need to attain.Consciousness raising in environmental thinking, and the ethical and aesthetic dilemmas posed by the global ecological crisis. The task of ecocriticism, is to express a conceptual foundation for the study of interconnections between literature and the environment. Through An Eco criticism viewpoint the researcher would like to discuss about the emotional and physical of characters Get along nature as essential for building development-based novel of ecological self.